Application of Social Skills Training for Dementia Patients Experiencing Social Isolation - Fahrizal, Yanuar; Daulima, Novy Helena; Mustikasari, Mustikasari (Jurnal Keperawatan Jiwa, 2024)
Alzheimer's disease is one type of degenerative brain disease, meaning it worsens over time and leads to dementia. The total number of new dementia cases occurs every four seconds. Indonesia is among the countries with a population structure trending towards aging. Dementia has negative economic impacts. Other potential impacts include behavioral and emotional changes. Behavioral and emotional changes in dementia patients can manifest as social inhibition and social-interpersonal alterations. Dementia patients tend to experience social isolation. Nursing intervention in the form of Social Skills Training is required to enhance socialization skills. The objective of this case study is to assess the impact of social skills training treatment on the manifestation of social isolation symptoms in individuals with dementia. This study was a case report with a descriptive observational design. The sample of the case report consisted of 2 dementia patients who met the inclusion criteria of experiencing difficulties in socialization and receiving social skills training therapy for five sessions. Changes occurred after receiving the nursing intervention of social skills training, namely a decrease in signs and symptoms of social isolation. Nursing intervention through social skills training can reduce signs and symptoms of social isolation in dementia patients.